Is there polarization in brazilian journals' Facebook posts during election campaign?: A comparative analysis of the provision Information about Brazilian presidential candidates in 2014 - Cervi, Emerson U. (2015)
This paper proposes a comparative analysis of presidential candidate's quotes from 12 Brazilian newspapers' fanpages, in order to identify, by region, the existence of bias against or in favor of a particular candidate. It was used predominantly a methodology of quantitative content analysis to study 34,618 newspapers' posts published, between July 1 and October 31, 2014, citing at least one of the three main presidential candidates: Aécio Neves (PSDB), Dilma Rousseff (PT) or EduardoCampos/Marina Silva (PSB). The variable used to test the hypothesis is the valence post citing candidates. The tests showed significant differences between the first and the second round in positions of newspapers by region.